2022
DOI: 10.1111/jasp.12880
|View full text |Cite
|
Sign up to set email alerts
|

The relation of climate change denial with benevolent and hostile sexism

Abstract: Ecofeminism purports that sexist ideology and climate change denial are related, as prejudice, and its desire for power and nonuniversalism, create a disregard for both.In three studies we examined the associations between hostile and benevolent sexism with climate change denial. The first study (n = 270) demonstrated that hostile sexism explained unique variance in climate change denial over and above two strong predictors of prejudice and climate change denial, social dominance orientation and right-wing aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
(177 reference statements)
1
2
0
Order By: Relevance
“…Although skepticism and denial are not synonymous, skepticism that persists in the face of reasonable evidence falls into the camp of motivated science rejection (Schmid & Betsch, 2019). We contend that our findings extend the field of science denial, including evidence that hostile sexism predicts resistance to other domains of scientific information (i.e., climate change; Nicol et al, 2022). Hostile sexism thus seems a generative avenue for understanding motivated rejection of science.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although skepticism and denial are not synonymous, skepticism that persists in the face of reasonable evidence falls into the camp of motivated science rejection (Schmid & Betsch, 2019). We contend that our findings extend the field of science denial, including evidence that hostile sexism predicts resistance to other domains of scientific information (i.e., climate change; Nicol et al, 2022). Hostile sexism thus seems a generative avenue for understanding motivated rejection of science.…”
Section: Discussionsupporting
confidence: 63%
“…Second, benevolent sexism remains an underexplored predictor of science denial. We focused solely on hostile sexism because it has been found to explain more unique variance in both science denial (Nicol et al, 2022) and attitudes towards rape (Agadullina et al, 2022). Nevertheless, assessing both facets of ambivalent sexism could reveal important outcomes.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Such an ecofeminist approach also asserts that power systems in society or cultural hegemonic values, lead to domination over women and over the environment (Bloodhart & Swim, 2010). Nicol et al (2022) in their survey studies with US participants found support for a strong correlation between HS and climate change denial, so that HS explained unique variance in climate change denial over and above SDO and RWA. Referring to the third largest country in the world that is also one of the largest environmental polluters, they suggest that given their results, reducing HS might be important to create a greater acceptance of climate change.…”
Section: Sexist Authoritarian and Climate Change Beliefs And Correlat...mentioning
confidence: 99%